Nutritional Supplements for the Treatment and Prevention of Sports-Related Concussion—Evidence Still Lacking. Issue 4 (July 2017) - Trojian, Thomas H.; Wang, David H.; Leddy, John J.
Abstract : Concussions are common neurologic events that affect many athletes. Very little has been studied on the treatment of concussions with supplements and medications. The U.S. Food and Drug Administration (FDA) reminds us that no supplement has been proven to treat concussions. Many animal studies show that supplements have potential for improving the effects of a brain injury but none have been shown to be of consistent benefit in human studies. Animal studies on severe traumatic brain injury (TBI) may not therefore be applicable transfer to sports-related concussions (SRC). Of the many supplements reviewed in this article, omega-3 fatty acids (Ω-3 FA) have potential for SRC treatment but in the one human trial those taking higher dosages preinjury had more concussions. In animal studies, postinjury administration was as effective as pretreatment. N -acetyl-cysteine has demonstrated a positive short-term effect on blast injuries in soldiers if administered within 24 h, but there are no studies in SRC. Caffeine, conversely, may be detrimental if taken after SRC. Lower serum levels of vitamins D, C, or E preinjury have worse outcomes in animal studies. Preinjury correction of deficiencies may be of benefit. Current human trials for nicotinamide ribose, melatonin, and branched chain amino acids (BCAA) may soon provide more evidence for the use of these supplements to reduce the impact of SRC in athletes.